Natural enemies of lepidopterous borers on maize and elephant grass in the forest zone of Cameroon - Ndemah, R.; Schulthess, F.; Poehling, M.; Borgemeister, C.; Goergen, Georg E. (CAB International, 2001)
The importance, geographical and temporal distributions of parasitoids of lepidopterous borers on maize and elephant grass, Pennisetum purpureum, were assessed during surveys in farmers’ fields in six villages and two on-station trials in the forest zone of Cameroon between 1995 and 1996. The borer species encountered were Busseola fusca (Fuller), Sesamia calamistis Hampson, Eldana saccharina Walker on both host plants, and Mussidia nigrivenella Ragonot on maize only. Busseola fusca was the predominant host accounting for 44–57% and 96% on maize and elephant grass, respectively, followed by E. saccharina on maize with 27–39%. Fifteen hymenopterous, two dipterous and one fungal species were found on these stem and cob-borers. Among those were six pupal, six larval, four egg, one larval–pupal parasitoid and four hyperparasitoids. The scelionid parasitoids Telenomus busseolae Gahan and T. isis Polaszek were found on B. fusca eggs in all locations. During the first season, mean egg parasitism was low and ranged between 3.1% and 27% versus 54–87% during the second season. Species belonging to the Tetrastichus atriclavus Waterston complex were recovered from all four borer species. The majority and most common larval and pupal parasitoid species belonged to the ingress-and-sting guild.Larval and pupal parasitism were very erratic and on more than 50% of the sampling occasions no parasitoids were recovered. Parasitoid diversity was higher on elephant grass than maize.